Cellulose degradation products and high ionic strength enhance the retardation of strontium in hydrated cement paste - Hinchliff, J.; Felipe-Sotelo, M.; Drury, D.; Evans, N.D.M.; Read, D. (Frontiers in Nuclear Engineering, 2022)
The present concept for the disposal of some low- and all intermediate-level radioactive waste in the United Kingdom involves grouting with cement in steel drums and placement in a geological facility. The vaults would then be backfilled with low strength, high porosity cement-based materials designed to promote a pervasive, alkaline environment in which many of the radioactive species present are sparingly soluble. This work investigates the interaction of strontium with such a backfill under both diffusive and advective conditions given the potential significance of the fission product 90Sr. An important characteristic of the United Kingdom waste inventory is the abundance of organic compounds, including cellulosic materials; consequently, the experiments were repeated with products of alkaline cellulose degradation. Additional experiments were performed at high ionic strength simulating anticipated changes in the salinity of the groundwater. The effective diffusivity (De) of strontium in the absence of the organic compounds ranged between 5.5 × 10−11 and 8.5 × 10−11 m2 s−1, with a distribution coefficient (Rd) of between 2.8 × 10−3 and 3.1 × 10−3 m3 kg−1. The presence of organic compounds and/or an increase of ionic strength enhanced the retardation of strontium. The results indicate that the retention of strontium by hydrated cement paste occurs via a reversible ion exchange mechanism rather than mineralisation and is promoted by decalcification of the calcium silicate hydrate phases.